Changes in in Vitro Methane Production and Fatty Acid Profiles in Response to Cakalang Fish Oil Supplementation - E. H. B. Sondakh; M. R. Waani; J. A. D. Kalele (Media Peternakan, 2017)
This experiment was conducted to determine the effect of cakalang fish oil addition in ruminant feed on in vitro methane production and fatty acid profiles. This experiment consisted of four treatments which were R0 : feed composing of forage and concentrate at a ratio of 60% : 40% without cakalang fish oil (CFO) addition as control feed; R1: R0 added with CFO at 2.5%; R2: R0 added with CFO at 5%, and R3: R0 added with CFO at 7.5%. Fermentation with rumen fluid was done using the Hohenheim Gas Test (HGT); feeds were incubated at 39 oC for 72 hours. At the end of fermentation, samples were obtained and methane production and fatty acid profiles were determined. The experiment was conducted in completely randomised design with four replications. Data were analysed using analysis of variance and differences among treatment means were analysed using Duncan multiple range test. Results showed that CFO supplementation affected (P<0.05) methane production, protozoa numbers and NH3 concentration; whereas the other parameters, i.e. VFA concentration, pH, and microbial protein were not affected. Some fatty acid profiles were influenced by treatments, such as palmitic, stearic, oleic, linoleic, and linolenic (P<0.05), while others, i.e. lauric and miristic were not affected. It is concluded that the best level of CFO supplementation is 5% as this level reduces methane production and increases unsaturated fatty acids without any negative effects on other variables measured.